2021
DOI: 10.3389/fnins.2021.721364
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cell Excitability of Cardiac Postganglionic Parasympathetic Neurons Correlates With Myocardial Infarction-Induced Fatal Ventricular Arrhythmias in Type 2 Diabetes Mellitus

Abstract: ObjectiveWithdrawal of cardiac vagal activity is considered as one of the important triggers for acute myocardial infarction (MI)-induced ventricular arrhythmias in type 2 diabetes mellitus (T2DM). Our previous study demonstrated that cell excitability of cardiac parasympathetic postganglionic (CPP) neurons was reduced in T2DM rats. This study investigated whether cell excitability of CPP neurons is associated with cardiac vagal activity and MI-induced ventricular arrhythmias in T2DM rats.MethodsRat T2DM was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Data from the power spectral analysis of the HRV demonstrated that HF power (an index of cardiac parasympathetic activation) was significantly reduced, whereas the LF power (a marker of cardiac sympathetic activation) was slightly reduced in T2DM rats, compared with sham rats ( Figure 7 ). These data are consistent with results from our recent publication ( 24 ) and one clinical report that vagal predominance was significantly impaired in proportion to a withdrawal of total autonomic activity ( 71 ). Ad.CAT gene transfection into CVP neurons partially restored T2DM-impaired cardiac vagal activation recorded in T2DM+Ad.CAT conscious rats ( Figures 7A,B ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Data from the power spectral analysis of the HRV demonstrated that HF power (an index of cardiac parasympathetic activation) was significantly reduced, whereas the LF power (a marker of cardiac sympathetic activation) was slightly reduced in T2DM rats, compared with sham rats ( Figure 7 ). These data are consistent with results from our recent publication ( 24 ) and one clinical report that vagal predominance was significantly impaired in proportion to a withdrawal of total autonomic activity ( 71 ). Ad.CAT gene transfection into CVP neurons partially restored T2DM-impaired cardiac vagal activation recorded in T2DM+Ad.CAT conscious rats ( Figures 7A,B ).…”
Section: Resultssupporting
confidence: 93%
“…Patients with T2DM are two to four times more likely to die from MI than non-diabetic patients ( 6 , 100 ). Our recent study found that the decrease in cell excitability of CVP neurons contributes to the withdrawal of cardiac vagal activity and MI-evoked ventricular arrhythmias and high mortality in T2DM rats ( 24 ). Our current study further demonstrated that endogenous H 2 O 2 elevation is a critical factor for dysfunction of CVP neurons and subsequent impairment of the cardiac vagal activity in the T2DM state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations